COMPARATIVE STUDY OF PTERYGIUM SURGERY - Cheleva, V; Stankovic Babic, G; Zdravkovska Jankuloska, M (Macedonian Academy of Sciences and Arts, 2011)
Aim: To compare and evaluate the success rates of various surgical techniques of pterygium excision, including pterygium excision with complete suture of conjunctivae (PESC), pterygium excision with conjunctival auto graft transplantation with graft from the inferior temporal bulbar conjunctiva (ITBC) and pterygium excision with conjunctival auto graft transplantation with graft from the superior temporal bulbar conjunctiva (STBC). Material and methods: 120 cases with primary unilateral nasal pterygium were evaluated. Outcomes were evaluated in terms of complication and recurrence after pterygium excision. The patients were divided into 3 groups: 1. Group of 40 patients with primary pterygium (pterygium’s length over the cornea 1,0 mm and more) treated by the technique of pterygium excision with complete suture of conjunctiva (PESC). 2. Group of 40 patients with primary pterygium (pterygium’s length over the cornea 1,0 mm and more) treated by the technique of pterygium excision with the conjunctival auto graft transplantation with graft from the inferior temporal bulbar conjunctivae(ITBC). 3. Group of 40 patients with primary pterygium (pterygium’s length over the cornea 1,0 mm and more) treated by the technique of pterygium excision with conjunctival auto graft transplantation with graft from the superior temporal bulbar conjunctivae(STBC). Results: Mean follow up time after the surgery was 15 months (6 to 24 months). 12 out of 40 (30%) recurred after the pterygium excision with complete suture of conjunctivae (PESC). Three out of forty (7,5%) pterygium recurred after the modified surgical techniques of pterygium excision with conjunctival auto graft transplantation with graft from the inferior temporal bulbar conjunctiva (ITBC). Five out of forty (10,2%) recurred after the pterygium excision with conjunctival auto graft transplantation with graft from the superior bulbar conjunctivae (STBC). All the recurrences (8 cases) in both pterygium groups treated by the transplantation procedures were after excision of progressive pterygium when the pterygium reaches more than 3 mm of corneae. Only one surgeon performed all 120 surgeries. Conclusion: A comparison of the group’s demonstrated that the recurrence rate was highest in the group without transplantation, using only complete suture of the conjunctiva. The excision of pterygium with conjunctival autograft transplantation from the inferior or superior temporal bulbar conjunctiva are highly efficient in terms of low recurrence rates. The modified surgical technique using the graft from the inferior temporal bulbar conjunctivae is preferred because the superior bulbar conjunctiva is intact for eventual future surgical intervention.
Keywords: pterygium; recurrence; primary; conjunctival autograft transplantation